2018
DOI: 10.1159/000489987
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Cholecystitis Reduces Interstitial Cells of Cajal in Porcine Gallbladder Through Decreased mRNA Synthesis

Abstract: Background/Aims: Acute cholecystitis is a common gastrointestinal disorder, often characterized by acute cholecystitis with gallbladder motility disorder. Interstitial cells of Cajal (ICCs) are the pacemaker cells of gut motility in the gastrointestinal tract. Disruption of ICC function is related to motility disorders. The aim of this study was to explore the cellular and molecular mechanisms of ICCs in acute cholecystitis and after the resolution of acute inflammation. Materials and Methods: Fifty adult guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The significant downregulation of SCF/c‐kit pathway is associated with a decrease in the number of gallbladder ICCs, increased apoptosis of gallbladder ICCs, and a decrease in the maintenance and regeneration of ICC networks (Hu, Luo, & Ding, 2009; Torihashi et al, 1999). Our previous study supports this, as inhibiting inflammation leads to the upregulation of the SCF/c‐kit pathway (Huang, Qiu, & Yu, 2018). Here we further found that the removal of stress allows kit receptors to recover, as the SCF/c‐kit pathway was upregulated and the number of gallbladder ICCs increased.…”
Section: Discussionsupporting
confidence: 75%
“…The significant downregulation of SCF/c‐kit pathway is associated with a decrease in the number of gallbladder ICCs, increased apoptosis of gallbladder ICCs, and a decrease in the maintenance and regeneration of ICC networks (Hu, Luo, & Ding, 2009; Torihashi et al, 1999). Our previous study supports this, as inhibiting inflammation leads to the upregulation of the SCF/c‐kit pathway (Huang, Qiu, & Yu, 2018). Here we further found that the removal of stress allows kit receptors to recover, as the SCF/c‐kit pathway was upregulated and the number of gallbladder ICCs increased.…”
Section: Discussionsupporting
confidence: 75%
“…Hemorrhage, edema, surface ulceration, and fibroblast proliferation were assigned scores of 0, 1, 2, and 3, representing no, mild, moderate, and severe conditions, respectively. The presence or absence of vascular dilation was noted and given a score of 1 if present and 0 if absent . Scores were summed and the final inflammation score ranged from 0 to 7.…”
Section: Methodsmentioning
confidence: 99%
“…The presence or absence of vascular dilation was noted and given a score of 1 if present and 0 if absent. 10 Scores were summed and the final inflammation score ranged from 0 to 7. The inflammation scores were determined by a pathologist in a blinded fashion at the Department of Pathology of the First Affiliated Hospital of Zhengzhou University.…”
Section: Histological Analysismentioning
confidence: 99%
“…ICC is generally considered as a pacemaker cell and a neuromuscular transmission medium of gastrointestinal activity. Studies have shown that ICC density in colon of patients with slow transit constipation is significantly lower than that of normal patients (Huang et al, 2018). Therefore, the decrease of ICC may lead to the lack of slow wave activity, which affects the contraction response and leads to delayed transmission in patients with slow transit constipation.…”
Section: Introductionmentioning
confidence: 98%